On Weakly P.P. Rings (Communications in Mathematical Research, 2021)
We introduce, in this paper, the right weakly p.p. rings as the generalization of right p.p. rings. It is shown that many properties of the right p.p. rings canbe extended onto the right weakly p.p. rings. Relative examples are constructed. Asapplications, we also characterize the regular rings and the semisimple rings in termsof the right weakly p.p. rings.